2017
DOI: 10.22159/ijpps.2017v9i7.18109
|View full text |Cite
|
Sign up to set email alerts
|

Antidyslipidemia and Antioxidant Activity of Andrographolide Compound From Sambiloto (Andrographis Paniculata) Herb

Abstract: Objective: The aim of this study was to observe the antidyslipidemic and antioxidant activity of andrographolide (AND) compound from Sambiloto (Andrographis paniculata) herb. The antidyslipidemic activity could be described by lowering TC (total cholesterol), TG (triglyceride), and LDL (low-density lipoprotein) level in the blood and by increasing HDL (high-density lipoprotein) level in the blood. The antioxidant activity could be described by inhibiting the ox-LDL (oxidized low-density lipoprotein) formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…-NF--ERK2 on platelets. [6,17,18] In this study, the Andrographis paniculata extract was shown to decrease the expression of TLR4 with a decreasing effect starting to appear in treatment group 1, namely at a dose of 18 mg/kg BW, and there was a tendency for effect to increase with increasing dose. It was found that the dose of Andrographis Vol.8; Issue: 10; October 2021 paniculata extract in treatment group 3 (40 mg/kg BW) gave the highest TLR4 reduction effect.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…-NF--ERK2 on platelets. [6,17,18] In this study, the Andrographis paniculata extract was shown to decrease the expression of TLR4 with a decreasing effect starting to appear in treatment group 1, namely at a dose of 18 mg/kg BW, and there was a tendency for effect to increase with increasing dose. It was found that the dose of Andrographis Vol.8; Issue: 10; October 2021 paniculata extract in treatment group 3 (40 mg/kg BW) gave the highest TLR4 reduction effect.…”
Section: Discussionmentioning
confidence: 59%
“…[6,7] Andrographolide showed the antiatherosclerosis effect of Andrographis paniculata also as an anti-inflammation and had a potent hypolipidemic effect by lowering total cholesterol levels such as triglycerides, HDL, and LDL. [6,7] Andrographis paniculata is also known to be able to reduce inflammation and is said to have antioxidant properties by preventing the production of free radicals. [4,8] The purpose of this study was to prove whether the administration of Andrographis paniculata extract could reduce the expression of Toll Like Receptor-4 in rats exposed to cigarette smoke and could reduce the incidence of aortic calcification in rats exposed to cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
“…In both in vivo and human clinical trials, AP can enhance lipid profiles by lowering total cholesterol, triglycerides, LDL, and boosting HDL blood levels. 16,20,21,23,29,30,34 . This ability is caused by AP inhibition of the HMG-CoA reductase enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…This compound becomes the point of interest since A. paniculata herb is widely used as a traditional medicine in several Asian countries such as India, Indonesia, China, Malaysia, and Thailand [1,2]. A large number of studies were conducted to isolate, identify, and quantify this substance [3][4][5] as well as assess its pharmacological activities [6][7][8], and its safety [9,10]. Andrographolide is reported to exhibit various biological activities, including antidiabetic [11], anticancer, anti-inflammatory [6], antivirus, and hepatoprotective activities.…”
Section: Introductionmentioning
confidence: 99%